Measurement properties of the product of investigator's global assessment and body surface area in children and adults with atopic dermatitis. (1st September 2020) - Silverberg, J.I.; Lei, D.; Yousaf, M.; Janmohamed, S.R.; Vakharia, P.P.; Chopra, R.; Chavda, R.; Gabriel, S.; Patel, K.R.; Singam, V.; Kantor, R.; Hsu, D.Y.
Abstract: Background: Multiple clinician‐reported outcome measures exist for atopic dermatitis (AD) severity. However, there is no gold standard for use in clinical practice. Objectives: To determine the measurement properties of the product of validated Investigator's Global Assessment for AD (vIGA) and body surface area (BSA) overall or divided into six categories (cBSA: 0%/0.1, <10%/10, <30%/30, <50%/50, <70%/70 and <90%/90–100%) and compare with other clinician‐reported and patient‐reported outcomes in adults and children with AD. Methods: We performed a prospective dermatology practice‐based study using questionnaires and evaluation by a dermatologist ( n = 653). Results: vIGA*BSA and vIGA*cBSA had good convergent validity with BSA (Spearman's ρ = 0.97 and 0.93), eczema area and severity index (ρ = 0.94 and 0.92), and objective SCORAD (ρ = 0.88 and 0.89); and weak‐to‐good convergent validity with Numeric Rating Scale average itch (ρ = 0.22 and 0.22) and worst itch (ρ = 0.27 and 0.28), Patient‐Oriented Eczema Measure (ρ = 0.44 and 0.43), Dermatology Life Quality Index (ρ = 0.48 and 0.49), ItchyQOL (ρ = 0.45 and 0.46), PROMIS Sleep Disturbance (ρ = 0.46 and 0.37) and sleep‐related impairment (ρ = 0.31 and 0.31) in adults and/or children; very good discriminant validity for physician‐reported global AD severity; good responsiveness to change of severity of AD and itch; and good reliability (intraclass correlation coefficient [95% confidence interval]: 0.72 [0.60–0.81] and 0.74 [0.62–0.82]) with no floor or ceiling effects. Thresholds for interpretability bands and clinically important difference were established. Conclusions: vIGA*BSA and vIGA*cBSA scores showed good convergent and discriminant validity, reliability, responsiveness and interpretability in adults and children with AD, and were feasible for use in clinical practice. vIGA*BSA and vIGA*cBSA had slightly lower convergent validity than EASI or objective SCORAD, but might be more efficient to collect and score.